Coupled Best Proximity Points under the Proximally Coupled Contraction in a Complete Ordered Metric Space - Kumam, Poom; Ansari, Arslan Hojat; Sitthithakerngkiet, Kanokwan (Communications in Mathematics and Applications, 2016)
In this paper, we prove the existence and uniqueness of a coupled best proximity point for mappings satisfying the proximally coupled contraction condition in a complete ordered metric space. Further, our result provides an extension of a result due to Luong and Thuan (Comput. Math. Appl. 62 (11) (2011), 4238–4248, Nonlinear Anal. 74 (2011), 983–992.